The Lung Allocation Score and Its Relevance - Lyu, Dennis M.; Goff, Rebecca R.; Chan, Kevin M. (Seminars in Respiratory and Critical Care Medicine, 2021)
Lung transplantation in the United States, under oversight by the Organ Procurement Transplantation Network (OPTN) in the 1990s, operated under a system of allocation based on location within geographic donor service areas, wait time of potential recipients, and ABO compatibility. On May 4, 2005, the lung allocation score (LAS) was implemented by the OPTN Thoracic Organ Transplantation Committee to prioritize patients on the wait list based on a balance of wait list mortality and posttransplant survival, thus eliminating time on the wait list as a factor of prioritization. Patients were categorized into four main disease categories labeled group A (obstructive lung disease), B (pulmonary hypertension), C (cystic fibrosis), and D (restrictive lung disease/interstitial lung disease) with variables within each group impacting the calculation of the LAS. Implementation of the LAS led to a decrease in the number of wait list deaths without an increase in 1-year posttransplant survival. LAS adjustments through the addition, modification or elimination of covariates to improve the estimates of patient severity of illness, have since been made in addition to establishing criteria for LAS value exceptions for pulmonary hypertension patients. Despite the success of the LAS, concerns about the prioritization, and transplantation of older, sicker individuals have made some aspects of the LAS controversial. Future changes in US lung allocation are anticipated with the current development of a continuous distribution model that incorporates the LAS, geographic distribution, and unaccounted aspects of organ allocation into an integrated score.
Keywords: LAS; lung allocation score; lung transplant; organ allocation; OPTN